Improving Performance Skills (Performance) Students of Class X TKJ SMK Swasta Mandiri Al Washliyah Silangkitang on Statistical Material Using a Problem Based Learning (PBL) - Manisem (Journal of General Education Science, 2023)
By applying the issue put together learning model with respect to material measurements, it is expected to further develop the learning results of arithmetic understudies in class X-TKJ SMK Swasta Mandiri Al-Washliyah Silangkitang semester II of the 2022/2023 scholarly year. A similar gathering was directed in each pattern of the two patterns of class activity research. A sum of 33 understudies from class X-TKJ became the examination subjects. The information examination strategy utilized spellbinding correlation between Cycle I and Cycle II using the percentage of math learning results. In view of the aftereffects of the review, advancing by using the Issue Based Learning (PBL) learning model can further develop understudies learning results on the measured material in mathematics subjects. The consequences of the primary pattern of understudies who finished 22 or 71% were pronounced passed. After enhancements were made in the execution of cycle II, there was an increment, in particular 30 or 88% of understudies who finished. This study was deemed successful due to its success in achieving classical completeness in less than 85% of students with KKTP 75.